Work analysis of point equipment of KS1002.00.000 project in continuous welded rail - Rybkin, V. V.; Lysak, V. A.; Burdiuzha, O. L. (Science and Transport Progress, 2011)
In the article the possibility of safe operation of the switch (project KC1002.00.000) in the jointless track affected by thermal forces is under study.